Evaluation of the in vitro susceptibility and emergence of mutants resistant to ciprofloxacin among multidrug resistant clinical isolates. - Lopes, C. A.; Mendes, R. P.; Curi, P. C.; Watanabe, D. S.; Decarlis, R. M.; Horácio, A.; Michelin, L. A.; Placidelli, B. A. (My University, 1993)
Two hundred and seventy-seven multidrug resistant clinical isolates [K. pneumoniae, (N = 87); E coli, (N = 30); Salmonella typhimurium (N = 100); P. aeruginosa, (N = 30); S. aureus, (N = 30)] from hospitalized patients specimens, were tested in vitro for sensitivity to Ciprofloxacin. Application of the disk diffusion test and determination of the minimal inhibitory concentration by the microdilution method indicated that, almost all isolates were sensitive to the drug. Overall, S. aureus and P. aeruginosa were the less sensitive organisms. Ciprofloxacin-resistant mutants occurred at frequencies of > or = 10(-5)/CFU.
Keywords: ciprofloxacin; antibiotic resistance; Brazil; comparative study; drug effect; Enterobacter infection; Enterobacteriaceae; Escherichia coli; genetics; Gram negative infection; human; isolation and purification; Klebsiella pneumoniae; microbiological examination; microbiology; Pseudomonas aeruginosa; Salmonella typhimurium; salmonellosis; Staphylococcus aureus; Staphylococcus infection; Ciprofloxacin; Comparative Study; Drug Resistance, Microbial; Enterobacteriaceae Infections; Human; Klebsiella Infections; Microbial Sensitivity Tests; Pseudomonas Infections; Salmonella Infections; Staphylococcal Infections